1992
DOI: 10.1521/pedi.1992.6.2.162
|View full text |Cite
|
Sign up to set email alerts
|

Personality Disorders Associated with Generalized Anxiety, Panic, and Recurrent Depressive Disorders

Abstract: Examination, the authors examined DSM-III-R personality disorders in 37 patients with generalized anxiety disorder (GAD), 40 with panic disorder (PD), and 38 with recurrent major depressive disorder (RD) in order to delineate personality disorders associated with these Axis I diagnoses. A higher proportion of PD than GAD and RD patients met criteria for one or more personality diagnosis (50% vs. 41% and 34%, respectively), and PD patients had a greater variety of personality disorders. Disorders within the "an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
1
1

Year Published

1994
1994
2016
2016

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(9 citation statements)
references
References 8 publications
(8 reference statements)
1
4
1
1
Order By: Relevance
“…According to our results, there was no significant difference between GAD patients and those with a variety of other diagnoses regarding the presence of 'any' personality disorder, nor did other studies, using different control groups, find significantly higher rates of 'any' personality disorder in GAD patients compared to those with panic disorder [28,51,52], obsessive-compulsive disorder [52] or recurrent depression [51]. The strong association of GAD with obsessive-compulsive and avoidant personality found in the present study confirms the results of a previous study by Mancuso et al [56].…”
Section: Discussioncontrasting
confidence: 70%
“…According to our results, there was no significant difference between GAD patients and those with a variety of other diagnoses regarding the presence of 'any' personality disorder, nor did other studies, using different control groups, find significantly higher rates of 'any' personality disorder in GAD patients compared to those with panic disorder [28,51,52], obsessive-compulsive disorder [52] or recurrent depression [51]. The strong association of GAD with obsessive-compulsive and avoidant personality found in the present study confirms the results of a previous study by Mancuso et al [56].…”
Section: Discussioncontrasting
confidence: 70%
“…In males, the most frequent disorder was the evasive personality disorder at the ratio of 25% together with the obsessivecompulsive personality disorder with the same ratio. Such findings are in line with the results of the studies indicating that the PD patients have, to begin with the evasive and dependent personality disorders, Class C personality disorders (43)(44)(45). Barzega et al (20) indicated that PD patients have at least one personality disorder at the ratio of 68.5% and there is no difference between genders.…”
Section: Discussionsupporting
confidence: 83%
“…Substance abuse disorder is also among the psychological disorder coexisting with PD (6). Furthermore, the ratio of comorbidity of the second axis personality disorders with the PD is about [40][41][42][43][44][45][46][47][48][49][50]. Especially Class C personality disorders, consisting the types such as avoidant, obsessive compulsive and dependent personality disorders are those coexisting with the illnesses of the individuals with PD (7,8).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have reported prevalence rates of personality disorders of 35% to 50% among patients with GAD [13,[95][96][97][98]. Compared with PD patients, GAD patients have been found to be more likely to have at least one personality disorder [13].…”
Section: Generalized Anxiety Disorder (Gad)mentioning
confidence: 99%